AN ANALYSIS OF PRONUNCIATION ERRORS MADE BY THE FOURTH SEMESTER STUDENT OF ENGLISH EDUCATION DEPARTMENT - Aldo Legi; Sanerita T. Olii; Sarah Kamagi (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
Abstract: The purpose of this study is to find out the kinds of errors made by students in pronouncing English and To find out the factors that causes these errors to occur. The researcher used qualitative research as method to analyze the data. The data were found from the students’ pronunciation of English Department at Universitas Negeri Manado in academic year 2020/2021. In analysis the data, the researcher used error analysis method by Corder as quoted by Ellis (1994: 48). There were some steps in applying the error analysis to analyze the data. The steps were 1) Collection of samples of learner language, 2) Identification of errors, 3) Classification of Error, 4) Explaining the Errors, 5) Evaluation of errors. Based on the result, researcher found 39 pronunciation errors made by the third semester student of English Education Department at Universitas Negeri Manado. The researcher also found out the factors that caused these errors to occur. The errors were caused by L1 native language disorder and the errors also caused by a lack of knowledge of the language that is the goal of learnig